Pembuatan Modelling 3d Dan Animasi Game Platform Menggunakan Software 3DS Max - Regita Firanti; Khairunnisa Khairunnisa; Yessi Fitri Annisah Lubis (UIN Sumatera Utara, 2021)
As The development of animation and games in today's world is growing rapidly. 3D animation is widely used for film making, games and advertisements. one of the popular games today is a platform game. The making of this platform game animation is expected to advance and introduce the development of 3D animation and the software it uses. The process of making the animation itself requires a story idea, scenario and storyboard. This animation is made with 3-dimensional modeling. At the stage of animating objects, careful planning is needed by determining the keyframe as the flow of an object from its initial state to its final state. Making 3D modeling and animation of this platform game using 3ds Max software. WondershareFilmora is used for video editing and sound rendering. Keywords: Animation, 3D Modeling, Game, Game Platform